Management of Oral Mucosal Red Lesions with Pathogenesis Considerations: Two Case Reports - Insyafiana, Anisa; Wahyuni, Indah Suasani (Odonto : Dental Journal, 2025)
Introduction: Red lesions on the oral mucosa occur due to various reasons related to the patient's condition, such as allergic reactions, autoimmune disorders, or systemic diseases. Red lesions cause pain, paresthesia, or are accompanied by erosion, thus disrupting the function and comfort of the mouth. Management of red lesions varies depending on the pathogenesis of the diagnosis and systemic conditions. This case report aims to describe the management of red lesions of the oral mucosa by considering the pathogenesis of both cases.Case: The first case is a 31 years old woman with a history of hyperthyroidism and is being treated thyrozole with a dose of 1x5 mg/day, while the second case is a 23 years old woman with a history of atopy. Both complained that the oral mucosa felt numb ,thick, and stiff, accompanied by red spots. Extraoral examination revealed dry lips in both cases and the second case was accompanied by erosion. Intraoral examination showed erythematous erosions on the upper and lower labial mucosa in both cases.Case management: the first case was given 0.025% hyaluronic acid mouthwash (3x10 ml/day), while the second case was given compound topical medication containing: lanolin, petroleum jelly, and dexamethasone (3-5x/day), as well as cetirizine tablet (1x10 mg/ day).Result: After treatment for 1 week, both patients experienced significant improvement, and after 3 weeks the lesions in both patients had healed.Conclusion Management of oral mucosal red lesions that takes into considered pathogenesis factors and systemic conditions in both cases shows satisfactory results.